Noninvasive Ventilatory Support 2017
DOI: 10.1183/1393003.congress-2017.pa1878
|View full text |Cite
|
Sign up to set email alerts
|

Sleep related respiratory events during non-invasive ventilation of patients with chronic hypoventilation

Abstract: A B S T R A C TBackground: Non-invasive ventilation (NIV) is increasingly used in the treatment of patients with chronic hypercapnic respiratory failure (CRF). Residual sleep related respiratory events under NIV such as obstructive or central apnea/hypopnea (AH), or patient-ventilator asynchrony (PVA), may compromise treatment efficacy and/ or comfort. Aims of study: 1/to quantify the frequency and describe the types of both AH and PVA in a large group of stable patients with CRF during night-time NIV; 2/to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In addition, some manufacturers have developed algorithms for automatic estimation of leaks and residual upper airway obstructions (UAO). Residual UAO is common in patients undergoing nocturnal NIV [125] and their lack of correction has been associated with increased mortality in amyotrophic lateral sclerosis patients [126]. UAO estimation by algorithms showed reasonable accuracy compared with polysomnography and manual scoring [127].…”
Section: Narrative Question 2: How Can Clinicians Monitor and Follow-mentioning
confidence: 98%
“…In addition, some manufacturers have developed algorithms for automatic estimation of leaks and residual upper airway obstructions (UAO). Residual UAO is common in patients undergoing nocturnal NIV [125] and their lack of correction has been associated with increased mortality in amyotrophic lateral sclerosis patients [126]. UAO estimation by algorithms showed reasonable accuracy compared with polysomnography and manual scoring [127].…”
Section: Narrative Question 2: How Can Clinicians Monitor and Follow-mentioning
confidence: 98%
“…Patients established on NIV frequently have upper airway obstruction or may develop it whilst on NIV. 18 To help clinicians diagnose residual apnoea events, manufacturers have included connectors for integrated overnight cardiorespiratory polygraphy given additional signals such as thoraco-abdominal belts.…”
Section: Niv Hardwarementioning
confidence: 99%
“…A recent pilot proof‐of‐concept clinical trial showed a trend towards greater improvements in daytime PaCO 2 , HRQoL and sleep quality when using simple gas exchange monitoring compared to advanced monitoring . Moreover, it was shown that the presence of PVA do not necessarily affect outcomes in patients with CHRF . Conversely, Adler et al .…”
Section: Practical Advice On Initiation and Follow‐up Of Hi‐nivmentioning
confidence: 99%